Optimization of treatment of patients with ischemic heart disease after suffering intervention in the coronary arteries - Karpenko, Y. I.; Blikhar, O. V. (Journal of Education, Health and Sport, 2016)
Karpenko Y. I., Blikhar O. V. Optimization of treatment of patients with ischemic heart disease after suffering intervention in the coronary arteries. Journal of Education, Health and Sport. 2016;6(8):560-566. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60962 http://ojs.ukw.edu.pl/index.php/johs/article/view/3774 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 26.08.2016. Optimization of treatment of patients with ischemic heart disease after suffering intervention in the coronary arteries Y. I. Karpenko, O. V. Blikhar Odesa national medical university, Odesa, Ukraine Abstract Each year increase number of patients with ischemic heart disease (IHD), according to this rising costs of treating this group of patients and increase amount of complications of IHD. Also is actual question of management of patients with IHD after surgery interventions, particularly after stenting or coronary artery bypass grafting (CABG). Risk factors are strongly increase in the patients with diabetes mellitus (DM) type 2. For them is more common damaging the coronary artery on big distance, violation of microcirculation and silent form of IHD. All this often lead to late diagnosis of IHD. Given the above, developing new methods of treatments for this cohort of patients. One of them - a method of cardiac shock wave therapy (CSWT). The mechanism of action of CSWT is based on a direct effect of shock waves at a specific segment of the heart, and remote influence on neoangiogenesis and improving the microvascularization. We compared the efficacy of treatment in patients with IHD and DM type 2 after CABG or stenting conducted on background of standard therapy compared with use in the treatment method CSWT. The effectiveness of treatment at this stage of work was evaluated by the number of angina attacks and contractile capacity of left ventricular according data of Echocardioscopy. The maximum efficiency of the method observed at 6 months of treatment with using CSWT. Long-term results in a reduction in angina and improving myocardial contractile capacity recorded in the group of patients treated with CSWT. Keywords: cardiac shock wave therapy, ischemic heart disease, diabetes mellitus type 2.